Peningkatan Kompetensi Guru Dalam Penyusunan Kurikulum Operasional Madrasah Di KKMA Pringgabaya-Sambalia - Rabiatul Hasanah; Mahsur Mahsur (Indonesian Publication Center, 2025)
This community service initiative focused on enhancing the capacity of madrasah teachers in developing a Madrasah Operational Curriculum aligned with the Independent Learning framework. The program utilized an andragogical approach, incorporating material delivery and interactive discussions. Conducted over one day on July 18, 2024, the activity aimed to equip participants with the necessary skills. The results demonstrated that participants were successfully able to construct the Madrasah Operational Curriculum as intended. This included identifying student needs and adhering to the Education Content Standards set by the government, thereby ensuring the compiled curriculum met expected quality benchmarks. Overall, this training was deemed successful in improving teacher competence in curriculum development. However, areas for improvement were identified, specifically regarding the allocation of time for discussions and the delivery of more varied materials.